Case studies of communications systems during harsh environments: A review of approaches, weaknesses, and limitations to improve quality of service. (February 2019) - EL Khaled, Zayan; Mcheick, Hamid
The failure of communications systems may cause catastrophic damage to human life and economic activities as people are unable to communicate with each other in a timely manner and with a convenient quality of service. Therefore, the exchange of information is more than necessary for people in their everyday life or during harsh environments to prevent the death and injury of thousands of individuals. The study of communications systems behavior in harsh environments helps to design or select more resilient technologies that are capable of operating in challenging conditions. This article reviews existing approaches, major causes of failure, and weaknesses of communications systems during extreme events. First, we highlight the importance of communications systems, and then we examine related works, how communication may fail, and the effect of this failure on human life in general and during extreme events response. Furthermore, we study and analyze how communications are used during various stages of extreme events, and we identify the main weaknesses and limitations that communications systems may suffer based on many case studies. To conclude, we identify and discuss relevant attributes, requirements, and recommendations for communications systems to perform with a suitable quality of service during harsh environments and to reduce risks of communication failure in challenging conditions.